Wasp Parasitoid Cotesia marginiventris (Cresson) (Insecta: Hymenoptera: Braconidae) - Andrei Sourakov; Everett Mitchell (EDIS)
This document is EENY-123, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 2000.